Epistemologické otázky fyziky: od antinómií čistého rozumu k expresívnym medziam jazyka - Kvasz, Ladislav (Organon F, 2004)
The aim of the present paper is to describe the fundamental epistemic ruptures, which occurred during the history of physics. Our approach is based on the reconstruction of the changes in the formal language of a particular physical discipline. We take into account aspects like the analytic, expressive or explanatory power, as well as analytic and expressive boundaries. One of the main results of our reconstruction is a new interpretation of Kant’s famous antinomies of pure reason. If we are prepared to relativise some of Kant’s antinomies, and instead of ascribing them to reason as such we relate them to the language of physics, it is possible to show, that these antinomies are relevant even for modern physics. Taking the form of a phenomenon, that we call the expressive boundaries of language are the antinomies a universal feature of all physical theories. This shows, that Kant in his antinomies pointed to a remarkable epistemological fact.